Acute Lymphoblastic Leukemia Presenting as Pituitary Apoplexy: A Case Report and Review of the Literature. (28th December 2021) - Gupta, Rahul; Bhattacharjee, Urmimala; Lekshmon, K. S.; Chaudhary, Shakun; Sharma, Prashant; Jandial, Aditya; Dutta, Pinaki
Abstract : Thrombocytopenia as a precipitating factor for pituitary apoplexy (PA) is very rare event. There are only five reported cases of PA secondary to thrombocytopenia caused by underlying haematological malignancy. Herein, we report a case of 60-year-old male presenting with acute-onset headache, bilateral vision loss, and ptosis. Computed tomography and magnetic resonance imaging revealed findings indicative of pituitary adenoma with apoplexy. He was noted to have thrombocytopenia, and bone marrow evaluation revealed precursor B-lineage CALLA-positive acute lymphoblastic leukemia. Accordingly, he was started on dexamethasone and vincristine but succumbed to Acinetobacter baumanii -related hospital-acquired pneumonia two weeks after initiation of chemotherapy. We performed a literature search and found five cases of pituitary apoplexy secondary to haematological malignancy-related thrombocytopenia. The usual age of presentation was in the 6 th to 7 th decade, and there was slight male preponderance. The underlying pituitary adenoma was either nonfunctioning or a prolactinoma, and in majority, the apoplexy event occurred after the diagnosis of haematological malignancy. The platelet counts at the time of PA were less than 30 × 10 9 /L in all, and the malignancy subtypes were acute or chronic myeloid leukemia and chronic lymphoid leukemia. The current case highlights the importance of careful evaluation for the cause of thrombocytopenia in a case of PA.